Students’ perceptions of native/non-native English-speaking EMI teachers: Are NS teachers better than NNS teachers? - Xu, Luyao; Xiao, Yangyu (Frontiers in Education, 2023)
Higher Education internalization has prompted a constant growth of EMI courses delivered by teachers with different cultural and linguistic backgrounds. Existing literature has revealed that native English-Speaker (NS) teachers and non-native English-Speaker (NNS) teachers have demonstrated different characteristics in EMI teaching. EMI students tend to have different perceptions of NS and NNS teachers’ teaching competencies and their English proficiency seems to influence their perceptions of NS and NNS teachers. However, as EMI is still a relevant new concept in China, how students’ self-perceived English proficiency impact their perceptions of NS teachers and NNS teachers’ teaching competencies is under-explored in the Chinese higher education context. This study investigates Chinese tertiary students’ perceptions of NS and local NNS teachers’ competencies in EMI teaching, and how these perceptions connect to their self-perceived English. Data was collected through semi-structured interviews with seven Chinese university students who enrolled in EMI courses. The study highlighted that student perceived these two groups of lecturers’ teaching competencies differ regarding their language proficiency and teaching methods. Furthermore, these perceptions can be influenced by students’ self-perceived listening and speaking proficiency. The findings provide insights for EMI implementation in Chinese Higher Education and suggestions for refining EMI teachers’ teaching expertise.